PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DANGAN KEPUASAN KERJA SABAGAI VARIABLE INTERVENING PADA KARYAWAN PT. SANGO CERAMICS INDONESIA - Suastika Krisnawan, I Made; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This study aims to analyze the effect of transformational leadership style and compensation on employee performance with job satisfaction as an intervening variable. Employee performance is the most important factor, but there is a decrease in the performance of PT. Sango Ceramics Indonesia. There is also a Research Gap which is the background for this research. The population in this study were employees of PT. Sango Ceramics Indonesia using non-probability sampling techniques in sampling with the sample size involved in this study amounted to 100 employees. This research uses descriptive and quantitative analysis methods and uses multivariate analysis tools so that it can provide complex variable analysis results through the Smart Partial Least Square (PLS) 3.3.3 application program. The results of this study indicate that the Transformational leadership style has a positive and significant effect on job satisfaction and also has a positive and significant effect on employee performance. Compensation has a positive but not significant effect on job satisfaction and also has a positive but not significant effect on employee performance. Job satisfaction has been shown to mediate the relationship between transformational leadership style and employee performance as well as the relationship between compensation and employee performance.